Packing Oblique 3D Objects - Pankratov, Alexander; Romanova, Tatiana; Litvinchev, Igor (Molecular Diversity Preservation International, 2020)
Packing irregular 3D objects in a cuboid of minimum volume is considered. Each object is composed of a number of convex shapes, such as oblique and right circular cylinders, cones and truncated cones. New analytical tools are introduced to state placement constraints for oblique shapes. Using the phi-function technique, optimized packing is reduced to a nonlinear programming problem. Novel solution approach is provided and illustrated by numerical examples.